QE evolution of bialkali photocathode at cryogenic temperature - Zhao, Yonglong; Ouyang, Dongming; Xie, Huamu; Liu, Kexin; Huang, Senlin (Frontiers in Physics, 2023)
Photocathode plays an important role in generating high brightness and low emittance electron beam and K-Cs-Sb photocathode is preferred in SRF injectors for its high quantum efficiency, long lifetime, and low thermal emittance. To predict the QE change of K-Cs-Sb at cryogenic temperature more correctly, we have modified the QE formula of Spicer’s photoemission model considering the temperature dependence of work function and mean free path of photocathode material, which is obtained by fitting experimental data. The calculated QE drop of about 90.1% at 36.4 K fits well with the measured QE change in DC-SRF photoinjector at Peking University. This improved formula could provide a method to evaluate the QE performance of semiconductor photocathodes at cryogenic temperature.